2022
DOI: 10.1142/s1793557122502369
|View full text |Cite
|
Sign up to set email alerts
|

Power graph of a finite group is always divisor graph

Abstract: The power graph is a special type undirected simple graph of a finite group G which has the group elements as its vertex set and two distinct vertices [Formula: see text] are adjacent if one is non-negative integral power of other. Vertex labeling of graph [Formula: see text] is a process of assigning integers to all its vertices subject to certain conditions. In simple words, vertex (edge) labeling is a function of all vertices (edges) to set of labels. Frequently, integers are used in labeling of vertices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Furthermore, the discussion on the degree formula of the power graph of some finite group can be found in [14]. Later, Takshak, et al [15] showed the new finding that if Γ G is a power graph of a finite group G, then it is a divisor graph. Kumar et al [7] have presented a complete and excellent survey of the power graph for some finite groups.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the discussion on the degree formula of the power graph of some finite group can be found in [14]. Later, Takshak, et al [15] showed the new finding that if Γ G is a power graph of a finite group G, then it is a divisor graph. Kumar et al [7] have presented a complete and excellent survey of the power graph for some finite groups.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various graphs associated with algebraic structures have been studied such as various properties of power graphs in [1][2][3][4][5], square element graphs in [6], square power graphs in [7], kth power graphs in [8], etc. A power graph of a finite group G is an undirected finite simple graph having a vertex set group G in which two distinct element vertices have an edge iff one is the power of the other.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kumar et al [10] have discussed a survey of the power graph for some finite groups. The fact that a power graph is always a divisor graph is presented in [22].…”
Section: Introductionmentioning
confidence: 99%